Hamstring Injury Trends in Major and Minor League Baseball: Epidemiological Findings From the Major League Baseball Health and Injury Tracking System. Issue 7 (29th July 2019) - Okoroha, Kelechi R.; Conte, Stan; Makhni, Eric C.; Lizzio, Vincent A.; Camp, Christopher L.; Li, Bernard; Ahmad, Christopher S.
Background: Hamstring strains are the most common injury for professional baseball players and can result in significant time on the disabled list. To date, no study has reported the current trends in hamstring strains in professional baseball. Hypothesis: Professional baseball players would have an increased incidence of hamstring strains from 2011 through 2016. Study Design: Descriptive epidemiology study. Methods: Injury data were prospectively collected from 2011 through 2016 for every Major League Baseball (MLB) and Minor League Baseball (MiLB) team and was recorded in the MLB Health and Injury Tracking System. Data collected for this study included date of injury, activity during injury, time lost, primary injury or reinjury status, and imaging findings as well as player demographic information related to level of play, age, and position for all hamstring injury events. Injury rates were reported as hamstring injuries per number of games. Results: From 2011 to 2016, there were 2633 hamstring strains in professional baseball players. The rate of hamstring strains increased in MLB from a low of 1 injury every 39 games in 2011 to a high of 1 injury every 30 games in 2016. In MiLB, there were 2192 hamstring strains, with 1 injury every 35 games in 2011 compared with 1 injury every 30 games in 2016. The majority of injuries occurred in the infielder positions (37.5%) and resulted from base running (>50%), most commonly from home to first base. The most common hamstring injury was a grade 2 injury to the distal biceps femoris. The mean time missed after a hamstring injury was 14.5 days. Grade 3 and grade 2 hamstring strains resulted in significantly more days missed compared with grade 1 injuries ( P = .005 and P = .002, respectively). The rate of recurrent hamstring injuries was 16.3% for MLB and 14.2% for MiLB. Recurrent hamstring injuries resulted in more time lost than primary injuries (mean, 16.4 vs 14.5 days, respectively; P = .02). A total of 42 injuries were treated with platelet-rich plasma, and 19 were treated with surgery. The number of injuries treated with platelet-rich plasma increased in successive years. Conclusion: The rate of hamstring strains in professional baseball players has increased over the past 6 years and has resulted in a significant loss of playing time. Study results indicated that these injuries are affected by injury characteristics, position played, running to first base, seasonal timing, and history of hamstring injuries.